The military's business designing military power for the future - Rasmussen, Mikkel Vedby (Cambridge University Press, 2015)
"If the military were a business would you buy shares? Over recent years, Western armed forces, particularly the US, have been costing more yet achieving less. At the same time, austerity measures are reducing defence budgets. This book uses defence data to examine the workings of modern Western militaries and explore what kind of strategies can overcome this gap between input and output. Instead of focusing on military strategy, Mikkel Vedby Rasmussen seeks to draw on the ideas of business strategy to assess alternative business cases - reforming military HR to combat instability in the 'Global South' or utilising new technologies to overcome the prohibitive costs of current systems. Analysing the philosophical, strategic and budgetary underpinnings of these alternatives, he concludes that a more radical break from current military organisational practices is needed which would allow them to fit within a nation's overall national security system without ever-increasing budgets"--